Party Communication in Routine Times of Politics: Issue Dynamics, Party Competition, Agenda-Setting, and Representation in Germany - Bevern, Simona (Springer, 2015)
Simona Bevern addresses the questions what and why political parties communicate in the time between elections, focusing on the dynamic rise and fall of policy issues. Despite the central role of political parties and the alleged importance of communication, only few scholars have taken a closer look at the content and dynamics of parties’ communication in routine times of politics. In this study, interactions between parties’ communication, their party competitors, the legislative agenda and public opinion are studied in Germany for the years 2004–2009, making use of a novel data set and quantitative methods.